BACKWARD WALKING TRAINING IMPROVES KNEE PROPRIOCEPTION IN NON ATHLETIC MALES (International Journal of Physiotherapy, 2017)
Background: Walking is a popular, convenient, and relatively safe form of exercise. Humans generally learn walking in forward direction with little difficulty, while walking in backward direction is necessary for normal activities of daily living and accommodates the body with different tasks. This study was conducted to compare between forward and backward walking training on peak torque of Quadriceps and Hamstring muscles and their effect on knee proprioception.Methods: Forty non athletic males, with mean age (21.87±1.76) years participated in this study, and were classified into two equal groups. Group (A) walked forward on treadmill while group (B) walked backward three times/week for a total six weeks. They were assessed by using Biodex system 3 to measure the concentric peak torque of Quadriceps and Hamstring muscles at angular velocities 60 and 180°/sec and the knee joint proprioception. The assessment was done twice for every subject (pre-study and after six weeks of gait training).Results: t-test revealed statistical significant increase in peak torque of Quadriceps and Hamstrings muscles in both groups after training at 60 and 180°/sec (p-value < 0.05). There was statistical significant improvement in knee proprioception in group B only p-value was (0.000).Conclusion: Both forward backward walking training improving the peak torque of quadriceps and hamstring muscles, while backward walking is better in improving knee proprioception accuracy.